Evaluation of the Developmental Toxicity Induced by E804 in Zebrafish Embryos - Wang, Rongchun; Liu, Kechun; Zhang, Yun; Chen, Xiqiang; Wang, Xue (Frontiers in Pharmacology, 2020)
E804, a derivative of indirubin, have multi-biological activities such as anticancer and anti-inflammatory activities, but little is known about its developmental toxicity. In this study, we investigated the toxicity of E804 on the developments of zebrafish embryos. Our results showed that E804 treatment caused a significant increase of the malformation rate compared with the control groups. Pericardial edema and curved body shape were the most morphological abnormalities observed in E804-treated group. The hatching rates and body length of the zebrafish larvae was significantly decreased in E804-treated groups. E804 also affect the development of heart, liver, phagocytes and vascular formation. Further studies showed that the level of reactive oxygen species was significantly increased. The activity of total superoxide dismutase decreased and the concentration of malondialdehyde were increased. Much more apoptotic cells were detected in E804-treated group, compared with the control. In addition, gene-expression results showed that the pathways of oxidative stress and apoptosis were provoked in E804 treated groups. Taken together, our findings will be helpful to understanding E804-induced developmental toxicity and the underlying mechanism.